The Urgency of Agrarian Reform Policy: A Study of the Impact of Land Access on Farmer Household Welfare - Heru Poppy Samosir; Jossy P Moeis (BHUMI: Jurnal Agraria dan Pertanahan, 2022)
Abstract: Inequality of land ownership is caused by unequal access to land. This study examined the impact of land access on total farmer's household expenditure. The Agrarian reform policy assumed open and expand access to land for groups of landless or near landless farmer households. Through state-led and market-led approaches, this research provided a categorization of access to land in two ways, which are access opening and access expansion variables with each sample coverage. Using the two periods difference-in-difference (DID) method, this study analyzed the impact of opening and expanding access to the total expenditure of farmer households using IFLS 2007 and 2014 data. The results showed that there is a significant difference in the total expenditures of farmer households due to the opening and expansion of access referring to the land distribution scheme (state-led approach), and there is no significant difference through the market-led approach. Therefore, agrarian reform policies need to be carried out by emphasizing the role of the state in implementing land redistribution to landless and small farmers.   Keywords: Agrarian reform, state-led approach, market-led approach, impact of land access, total farmer household expenditure